2006
DOI: 10.1002/env.771
|View full text |Cite
|
Sign up to set email alerts
|

A model for external drift kriging with uncertain covariates applied to air quality measurements and dispersion model output

Abstract: SUMMARYWe present a method that combines uncertain air quality measurements with uncertain secondary information from an atmospheric dispersion model. The method combines external drift kriging and a measurement error (ME) model, and uses Bayesian techniques for inference. An illustration with simulated data shows what can theoretically be expected. The method is flexible for assigning different error variances to both the primary information and secondary information at each location. Next, we address actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Empirical models may give accurate results, but are restricted to the conditions under which they are developed (Manders, Schaap and Hoogerbrugge, 2009). Assimilating monitoring station observations and CTM output, with appropriate bias adjustments, has been shown to provide improvements over using either data source alone (van de Kassteele and Stein, 2006;Denby et al, 2008;Candiani et al, 2013;Hamm et al, 2015). In such settings, the CTM output enters as a model covariate and the measured station observations are the re- sponse.…”
mentioning
confidence: 99%
“…Empirical models may give accurate results, but are restricted to the conditions under which they are developed (Manders, Schaap and Hoogerbrugge, 2009). Assimilating monitoring station observations and CTM output, with appropriate bias adjustments, has been shown to provide improvements over using either data source alone (van de Kassteele and Stein, 2006;Denby et al, 2008;Candiani et al, 2013;Hamm et al, 2015). In such settings, the CTM output enters as a model covariate and the measured station observations are the re- sponse.…”
mentioning
confidence: 99%
“…Measurements made with instruments at monitoring stations are considered authoritative; however, these observations are often too sparse to deliver regional maps at sufficient resolution to assess progress with mitigation strategies and for monitoring compliance. One solution is to couple spatially sparse monitoring station observations with spatially complete chemistry transport model (CTM) output, (see, e.g., van de Kassteele and Stein 2006;Denby, Schaap, Segers, Builtjes, and Horalek 2008;Candiani, Carnevale, Finzi, Pisoni, and Volta 2013). In such settings, monitoring station observations serve as a regression model outcome with CTM output set as a predictor.…”
Section: Analysis Of Air Pollution Datamentioning
confidence: 99%
“…There are few and recent applications of geostatistical methods on transportation data. It can be observed that most available papers refer to traffic engineering studies (Ciuffo et al 2011;Mazzella et al 2011;Zou et al 2012), vehicle emission gases (Pearce et al 2009;Kassteele and Velders 2006;Kassteele and Stein 2006), and traffic injuries (Gundogdu 2014;Manepalli and Bham 2011;Molla et al 2014). Although in the 1990s, there were some studies in the literature on travel demand forecasting with applications of estimation techniques related to kriging (Ickstadt et al 1998), this approach is still recent and has not yet been sufficiently investigated in the line of research of transportation planning (Yoon et al 2014;Chen et al 2015).…”
Section: Introductionmentioning
confidence: 99%